Hubungan Kinerja Tugas dan Kinerja Kontekstual Dengan Kepuasan Kerja, Komitmen dan Kepribadian - D. Wahyu Ariani (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2010)
This study addressed the role of organizational commitment, job satisfaction and personality in contextual performance (organizational citizenship behavior) and task performance or in- role performance. Job satisfaction were identified satisfaction to reward and organizational commitment were identified affective organizational commitment and self-esteem personality, I provide a framework showing these variables may motivate citizenship behavior and in-role performance. A survey was conducted by using questionnaires from previous research. The questionnaires were sent to 250 employees in service organizations such as hospitals, schools, hotels, and educational institution. Validity tests and reliability tests were used to test the questionnaires contents. The Structural Equation Modelling (SEM) was used to test the relationship among the variables. The result proved that self-esteem personality have the strongest effect on individual in-role performance, and organizational commitment have the dtrongest effect on individual contextual performance (organizational citizenship behavior). In-role performance is different from contextual performance. . A thorough discussion on the relationship among the variables as well as on self rating is presented in this paper.